Photocatalytic magnetic separable beads for chromium (VI) reduction - Idris, Ani (2010)
Magnetically separable photocatalyst beads containing nano-sized iron oxide in alginate polymer were prepared. This magnetic photocatalyst beads are used in slurry-type reactors. The magnetism of the catalyst arises from the nanostructured particles ?-Fe2O3, by which the catalyst can be easily recovered by the application of an external magnetic field. These synthesized beads are sunlight-driven photocatalyst. In the system without magnetic photocatalyst beads, no chromium reduction was observed under sunlight irradiation due to the stability of the chromium (VI). Upon the addition of magnetic photocatalyst beads, the photo-reduction of Cr(VI) was completed in just after only 50 min under sunlight irradiation due to the photocatalytic activity of the beads. However when placed away from sunlight, the reduction rate of the chromium is just about 10%. These observations were explained in terms of absorption occurrence of chromium (VI) onto the catalyst surface which took place in this reaction. In addition, photo-reduction rate of chromium (VI) was more significant at lower pH. The results suggest that the use of magnetic separable photocatalyst beads is a feasible strategy for eliminating Cr(VI).